2020
DOI: 10.1016/j.neuroscience.2020.04.048
|View full text |Cite|
|
Sign up to set email alerts
|

Brain Structural Connectivity Predicts Brain Functional Complexity: Diffusion Tensor Imaging Derived Centrality Accounts for Variance in Fractal Properties of Functional Magnetic Resonance Imaging Signal

Abstract: The complexity of brain activity has recently been investigated using the Hurst (H) exponent, which describes the extent to which functional magnetic resonance imaging (fMRI) blood oxygen-level dependent (BOLD) activity is self-similar vs. complex. For example, research has demonstrated that fMRI activity is more complex before than after consumption of alcohol and during task than resting state. The measurement of H in fMRI is a novel method that requires the investigation of additional factors contributing t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…We observed that compared to HCs, significant decreases in FA and increases in RD were widespread over areas of the whole-brain WM skeleton in both TN wNVC and TN woNVC. Regarding TN wNVC, decreases in FA were coupled with increases in RD in areas of the corpus callosum, corona radiata and internal capsule, which indicates probable damage to pain integration, cognitiveaffective, and motor functions, also could be relative to compensatory mechanisms for this type of TN [40,41]. In addition, increases in RD in the areas of the posterior thalamic radiation, which is suggestive of damage to the microstructural properties of the thalamicsomatosensory.…”
Section: Widespread Compromise Of Wm Integrity Occurs In Both Tn Wnvcmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that compared to HCs, significant decreases in FA and increases in RD were widespread over areas of the whole-brain WM skeleton in both TN wNVC and TN woNVC. Regarding TN wNVC, decreases in FA were coupled with increases in RD in areas of the corpus callosum, corona radiata and internal capsule, which indicates probable damage to pain integration, cognitiveaffective, and motor functions, also could be relative to compensatory mechanisms for this type of TN [40,41]. In addition, increases in RD in the areas of the posterior thalamic radiation, which is suggestive of damage to the microstructural properties of the thalamicsomatosensory.…”
Section: Widespread Compromise Of Wm Integrity Occurs In Both Tn Wnvcmentioning
confidence: 99%
“…In TN wNVC, the brain connections of temporal gyrus, occipital lobe, insula, and thalamus are related to multisensory integration of auditory, visual, olfactory, and somatosensory information [43]. Altered connectivity in these regions may interfere the temporal filtering of nociceptive information in offset analgesia [39], and underlie the psychological disturbances including anxiety, fear, and panic in TN patients [41], and sensory, cognitive-affective, and modulatory aspects of pain [30]. However, patients with TN woNVC exhibited higher local network integration in the hippocampus, PFC and angular gyrus as compared to HC, which may undermine the spatial filtering of nociceptive information in CPM, especially the top-down pain processing [39].…”
Section: Widespread Compromise Of Wm Integrity Occurs In Both Tn Wnvcmentioning
confidence: 99%
“…These regions are anatomically and widely connected through fiber tracts, such as the superior longitudinal fasciculus, fronto-occipital fasciculus, and fasciculus uncinatus, all of which have been found to be impairment in CTN patients ( DeSouza et al, 2014 , Liu et al, 2018 ). The alterations of these areas may reflect cognition-related perception and analgesia modulation ( Andica et al, 2020 , Iwata et al, 2005 , Seminowicz et al, 2004 ), multisensory integration ( Chiapparini et al, 2010 ) or the psychological complaints of chronic pain ( Neudorf et al, 2020 ). Overall, our findings indicate that the white matter related SN was more vulnerable than the FN in CTN patients, wherein the disorders of peripheral regions involving multiple networks mainly affected global information integration.…”
Section: Discussionmentioning
confidence: 99%
“…Functional connectivity centrality has been used to demonstrate age and sex related differences (Zuo et al, 2012), differences between patient and control groups (for patients with schizophrenia, Chen et al, 2015;bipolar disorder, Deng et al, 2019, Zhou et al, 2017retinitus pigmentosa, Lin et al, 2021; and diabetic optic neuropathy, Xu et al, 2020), and differences related to genotype (Wink et al, 2018). Structural connectivity centrality has also been used to demonstrate differences between patient and control groups (for patients with prenatal alcohol exposure, Long et al, 2020; traumatic brain injury, Raizman et al, 2020;gut inflamation, Turkiewicz et al, 2021;and brain tumours, Yu et al, 2016), and to demonstrate a relationship between structural centrality and functional complexity (e.g., Hurst exponent; inversely related to fractal dimension, where a fractal dimension exceeding the topological dimension of the signal indicates complex functional activity) suggesting that regions integrating information from many sources have more complex functional activity (Neudorf et al, 2020). An important question that has not yet been explored, to our knowledge, is to what extent variance in functional connectivity-based centrality measures can be accounted for by structural connectivity and structural connectivity-based centrality.…”
Section: Learning Model Of Functional Connectivity and Centrality Based On Structural Connectivitymentioning
confidence: 99%